Triazolate counter ions in au' complexes: catalysts with improved thermal stability - Hashmi, A. Stephen K.; Lothschütz, Christian (ChemCatChem, 2010)
Counter revolution: Most homogeneous gold-catalyzed transformations employ gold(I) complexes with weakly coordinating anions, which, their remarkable activity notwithstanding, lack stability at higher temperatures. Shi et al. have described the synthesis of simple phosphine-based gold(I) complexes with triazolates as counter ions. The compounds are highly thermostable and good catalysts for intermolecular hydroaminations.
First published: 01 February 2010
Gesehen am 24.03.2023